Performance and Health Profile of IPB-D1 Chickens Supplemented With Cassava (Manihot Esculenta Crantz) Leaf Extract via Drinking Water: Performa dan Profil Kesehatan Ayam IPB-D1 yang Disuplementasi dengan Ekstrak Daun Singkong (Manihot Esculenta Crantz) melalui Air Minum (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2025)
This study evaluated the effects of cassava (Manihot esculenta Crantz) leaves extract (CLE) in drinking water on the performance and health profile of IPB-D1 chickens. Cassava leaves are known to contain bioactive compounds such as flavonoids, tannins, and saponins which have antioxidant and antibacterial properties. These compounds can provide positive effects such as feed efficiency, improving growth performance and health status of chickens by improving the immune system and reducing oxidative stress. Cassava leaves extract acts as a phytogenic additive that can be given in livestock drinking water. This study used 180 IPB-D1 chickens aged 2–8 weeks were randomly assigned to three treatments: CLE0 (control), CLE1 (17 ml/l CLE), and CLE2 (50 ml/l CLE). Parameters observed included growth performance, organ morphometry, hematological profiles, and ileal histology. Data were analyzed using one-way ANOVA and Tukey’s post hoc test (p